The case for an intermediate exchange rate regime with endogenizing market structures and capital mobility: The empirical study of Brazil - Annina Kaltenbrunner; Machiko Nissanke (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
Set in the context of the recent theoretical and policy debates on appropriate exchange rate regimes for emerging market economies in a world of free capital mobility, the paper attempts to present the case for an intermediate exchange rate regime, drawing on recent theoretical and empirical literatures on behavioural finance and currency market structures; and to examine empirically the experiences and evolution of Brazil's foreign exchange market under different exchange rate regimes.
Keywords: E44; F31; F41; O24; 330; exchange rate management; emerging markets; Brazil; Wechselkurssystem; Aufstrebende Märkte; Kapitalmobilität; Brasilien